2021
DOI: 10.1242/jeb.234351
|View full text |Cite
|
Sign up to set email alerts
|

Effects of wave-driven water flow on the fast-start escape response of juvenile coral reef damselfishes

Abstract: Fish often evade predators with a fast-start escape response. Studies typically examine this behaviour in still water despite water motion being an inherent feature of aquatic ecosystems. In shallow habitats, waves create complex flows that likely influence escape performance, particularly in small fishes with low absolute swimming speeds relative to environmental flows. I examined how wave-driven water flow affects the behaviour and kinematics of escape responses in juveniles of three coral reef damselfishes … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 97 publications
(98 reference statements)
0
1
0
Order By: Relevance
“…More advanced studies using advanced technological tools can be found in [15,[19][20][21][22][23][24]. More specifically, fundamental biological studies that provide information and data about the function of the paired fins during locomotion of the fish can be found in [25][26][27][28][29].…”
Section: Introductionmentioning
confidence: 99%
“…More advanced studies using advanced technological tools can be found in [15,[19][20][21][22][23][24]. More specifically, fundamental biological studies that provide information and data about the function of the paired fins during locomotion of the fish can be found in [25][26][27][28][29].…”
Section: Introductionmentioning
confidence: 99%